2016
DOI: 10.1002/jctb.4990
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic adsorption separation process: an alternative method of mercury extracting from aqueous solution using modified chitosan coated Fe3O4 nanocomposites

Abstract: BACKGROUND: In the present work, Hg (II) is considered as one of the most dangerous elements being released excessively into the environment from various sources. Therefore, the aim of this study is the removal of Hg (II) from wastewater effluent by synthesizing a magnetic chitosan modified with glutaraldehyde (MCS-GA) as an adsorbent. The composite structure was characterized using SEM/EDAX, FTIR, and XRD techniques. The adsorbent was tested by a batch system to determine the optimum conditions for removing H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…A limited number of studies have employed RSM approaches to optimize the generation of magnetic nanoparticles for enzyme immobilization. RSM keeps the number of experiments to a minimum for a relatively large number of significant factors as compared to those involving the simple, time consuming "one factor at a time" design [18].…”
Section: Resultsmentioning
confidence: 99%
“…A limited number of studies have employed RSM approaches to optimize the generation of magnetic nanoparticles for enzyme immobilization. RSM keeps the number of experiments to a minimum for a relatively large number of significant factors as compared to those involving the simple, time consuming "one factor at a time" design [18].…”
Section: Resultsmentioning
confidence: 99%
“…In these equations, R is the percentage of eliminated dye, C 0 is the initial dye concentration (mg/l), C e is the concentration of the remaining dye in the solution (mg/l), q t is the amount of adsorbed dye during time (mg/g), q e is the amount of adsorbed dye in the equilibrium status (mg/g), V is the solution volume (l), and M is the adsorbent dose (g). The present study focused on the impact of the initial dye concentration (20,40,50, and 60 mg/l), pH (4,7,9), adsorbent dose (0.1, 0.3, 0.5, 0.7, 1, and 1.5 g/l), and exposure time (10,20,30,40,60,90, and 120 min) were examined [9,15,21]. To come up with the optimal condition, the impacts of adsorbent dosage (0.1, 0.3, 0.5, 0.7, and 1 g/l), pH (2, 7, and 9), concentration (20,40,50, and 60 mg/l), and exposure time (10,20,30,40,60,90, and 120 min) were measured.…”
Section: Methodsmentioning
confidence: 99%
“…In their study, Justin et al attributed the frequencies of 2θ = 11 and 2θ = 20 to chitosan [28]. Also, Kumar et al [21] indicated that the frequency of 2θ = 21.18 has to do with chitosan graphene oxide.…”
Section: Sem Analysismentioning
confidence: 98%
“…Some macromolecules can form well-organized organic functional group chains by self-assembly ways and these are combined with other active matters to make synergetic effects of adsorption. [57][58][59][60] Asif et al synthesized a nuclearshell hybrid material containing iron nanoparticles coated with chitosan and calixarene composite. 61 The organic calixarene macromolecules possess adsorptive activity.…”
Section: Chemical Adsorption For Hg(ii) Removalmentioning
confidence: 99%